Indicators of morphological status of 6–8 year-old сhildren - Kholodov, Serhii (Journal of Education, Health and Sport, 2017)
Topicality. As many experts note, the processes of growth and development are biological properties of living matter. Human growth and development is a continuous progressive process that takes place throughout all life. Due to this, development occurs abruptly; thus, the difference between its individual stages or life periods presupposes not only quantitative, but also qualitative changes. Signs of physical development change under the influence of inherited features as well as under the influence of a complex set of social and demographic conditions. The task of the study is to determine morphometric parameters of almost healthy children, aged 6–8 years. The results of the research have found out that the average length and weight of boys’ and girls’ body naturally increase with age. This increase is continuous, although uneven. During the study period of ontogenesis, boys' body length increased by an average of11 cm, and girls by8.7 cm respectively. At the same time, body weight of both boys and girls has increased by an average of4.8 kg. Analysis of the data shows that in terms of length and body weight there are no statistically significant differences (p> 0.05) between boys and girls of all age groups within 6-8 year period. Conclusion. The analysis of a huge scope of scientific findings allows us to state that at a choice of control influences, development of prognostic models applied for estimation of children’s motility it is necessary to consider peculiarities of application of numerous means, methods and forms of physical training arrangements in various age periods as far as they can vary in one age period, depend on hereditary factors, environmental conditions and a number of other indicators. In our opinion, among the applied problems, the solution of which can be influenced by the results of this study the following should be mentioned, i.e. correction of motility disorders for 6–8 year-old children by means of modern biomechanical technologies.